Pathogenicity of Edwardsiella tarda to Anguilla marmorata - Syafitrianto, Irmawan; Rusaini, Rusaini (FAPETKAN UNTAD, 2019)
The pathogenicity of warm-water fish bacteria, Edwardsiella tarda in eel (Anguilla marmorata) was investigated. This study was designed using a completely randomized design (CRD) with three treatments of E. tarda concentration (2.52 × 107, 105, 103 cfu/mL) and three replicates. Regression analysis showed that the lethal concentration fifty (LC50) of E. tarda in eel was 2.56 × 104 cfu/mL. The mortality of eel in all treatments occurred 24 hours after injection. Clinical signs of disease in infected eel were melanization, inflammation, necrosis, pale liver, exopthalmus, ascites, and petechial haemorrhage.Keyword: Anguilla marmorata, Edwarsiella tarda, pathogenicity, lethal concentration.